Assessment of dexterity, motor coordination and impact on quality of life in patients using assistive technology: a case study (Research, Society and Development, 2020)
Introduction: Amputations are considered as total or partial withdrawal, having traumatic or congenital etiological causes, which end up impacting the individual's body acceptance and social relationships. The prostheses already existing in the scope of assistive technology, and new models, started to have an extensive acquisition value, becoming laborious to be acquired. As a result of this factor, companies such as e –NABLE together with health and engineering professionals aim to manufacture low cost upper limb prostheses, through additive manufacturing. Objective: perform an assessment of dexterity, motor coordination and impact on quality of life, in a patient using assistive technology. Methodology: The present study was characterized as a case study of a patient with transradial congenital amputation, who, through the 3D Hands project, received a low-cost prosthesis, where this research had as objective through the procedures and tests reported to assess dexterity, motor coordination and quality of life. Results and Discussion: It was observed that the use of the “Cyborg Beast” prosthesis was not satisfactory for the patient with congenital transradial amputation, with no expected tests being applied. However, since the patient had a lower score in the domain for emotional aspects, in the SF-36 Questionnaire, performed before the attempt at fitting. Conclusion: The importance of developing prosthetic models that serve this population was explained, as well as more studies that address motor coordination, manual dexterity and quality of life.